2003
DOI: 10.1038/sj.ejhg.5201038
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the French National Registry of unrelated bone marrow donors, using surnames as a tool for improving geographical localisation of HLA haplotypes

Abstract: The first statistical analysis of the French National Registry of volunteer bone marrow donors estimated the probabilities of haplotype frequencies separately for each of the 20 administrative regions of France. Here we propose to use donors' surnames to increase the accuracy of location of the donor's geographical origin. This approach allows us to estimate haplotype frequencies for administrative entities (90 departments) smaller than regions and to correct for bias resulting from recent mobility. We analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
5
0
2
Order By: Relevance
“…In addition, surnames can often reveal aspects of large-scale population structure; for example, a good correspondence exists between changes in surname distribution and linguistic boundaries [2], [3], [4], [5], [6]. Given the paternal inheritance of surnames in many societies, surnames also have demonstrable utility as proxies for genetic information [7], [8], [9], [10], [11]. As has been demonstrated by [12], this offers enormous potential, especially in the context of developing more efficient sampling strategies in the context of population genetics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, surnames can often reveal aspects of large-scale population structure; for example, a good correspondence exists between changes in surname distribution and linguistic boundaries [2], [3], [4], [5], [6]. Given the paternal inheritance of surnames in many societies, surnames also have demonstrable utility as proxies for genetic information [7], [8], [9], [10], [11]. As has been demonstrated by [12], this offers enormous potential, especially in the context of developing more efficient sampling strategies in the context of population genetics.…”
Section: Introductionmentioning
confidence: 99%
“…These studies were not very successful at predicting disease risk, but they highlighted some important aspects of the genetic architecture of common diseases. First, they showed that there existed some important genetic variability between populations with differences of allele frequency and linkage disequilibrium observed at all geographic scales, between continents but also between countries within a continent, and even within a country [ 2 , 3 , 4 ]. The important role of our immune system in our biological functioning and the selective response to environmental attacks and large epidemics probably explain this great variability [ 5 ].…”
Section: From the Early Days Of Human Genetics To The Birth Of Polyge...mentioning
confidence: 99%
“…; Degioanni et al . ; Jobling ). Scientists have recognised ever since the 19th century that many surnames are associated with distinctive population characteristics, and their association with genetic variation developed in the late 20th century (Lasker , 6).…”
Section: Introductionmentioning
confidence: 99%